Elasticidade de transmissão de preço no mercado internacional do petróleo e óleo de soja - Silva, Ester Fernanda da (2020)
With the increase in the use of biofuels in the world energy matrix, highlighting the biodiesel, the relationship between the prices of food commodities involved in energy production has a new empirical relevance. This work aimed was to measure and analyze the price transmission elasticity in the international petroleum and soybean oil market with monthly data from January 1980 to August 2019. Based on concepts of theories and market integration, we estimated econometric tests, among wich: unit root tests, cointegration, causality, error correction model (VECM) and impulse response function. The results show the absence of a relationship between these variables in the short term, whereas in the long term, the relationship exists. It was possible to verify that shocks in the prices of petroleum and soybean oil respond with volatility to each lagged month in the markes.